An Assessment of Demand for a Combined PharmD-MBA Program at the University of Saskatchewan - Kerry Mansell; Antoine Bruneau-Bouchard; Vincent Bruni-Bossio (MDPI AG, 2016)
(1) Background: Combined MBA programs are becoming increasingly popular, and it is anticipated that there will be 60 combined pharmacy-MBA programs across North America in 2015. We aimed to see if there would be support for a combined PharmD-MBA program at the University of Saskatchewan. (2) Methods: A questionnaire was distributed to 1st, 2nd, and 3rd year pharmacy students at the University of Saskatchewan. A separate questionnaire was developed and all practicing pharmacists in Saskatchewan were emailed a link to SurveyMonkey® (Palo Alto, CA, USA) to fill it out online. In-person and phone interviews were conducted with pharmacy stakeholders in Saskatchewan and across the country. (3) Results: Of the 265 students, 193 (72.8%) were present on the days the questionnaires were distributed, and they all completed the questionnaires. When asked if they would have pursued a combined degree if the U of S had offered it when they entered the pharmacy program, 16.6% (32/193) and 37.3% (72/193) either strongly agreed or agreed and 29.0% (56/193) were unsure. When pharmacists were asked if an MBA would be valuable or applicable in their current job, 42.2% (128/303) agreed and 13.9% (42/303) strongly agreed. When asked if they felt students graduating with a combined degree would be at an advantage for certain job opportunities upon graduation, 33.6% (100/298) strongly agreed and 55.4% (165/298) agreed. A total of 8 interviews were conducted with key stakeholders from across Canada. Of these 8 stakeholders, only 2 were aware that other combined programs were offered. All of the stakeholders were in favour of the idea of a combined degree. Some felt it was important for the program to have a clear value proposition and healthcare related content would be desirable. (4) Conclusions: Overall, pharmacist, pharmacy student, and stakeholder input indicate that a combined program could be supported at the University of Saskatchewan.